Murine Salivary Amylase Protects Against Streptococcus mutans-Induced Caries - Culp, David J.; Robinson, Bently; Cash, Melanie N. (Frontiers in Physiology, 2021)
Saliva protects dental surfaces against cavities (i.e., dental caries), a highly prevalent infectious disease frequently associated with acidogenic Streptococcus mutans. Substantial in vitro evidence supports amylase, a major constituent of saliva, as either protective against caries, or supporting caries. We therefore produced mice with targeted deletion of salivary amylase (Amy1) and determined the impact on caries in mice challenged with S. mutans and fed a diet rich in sucrose to promote caries. Total smooth surface and sulcal caries were 2.35-fold and 1.79-fold greater in knockout mice, respectively, plus caries severities were 2-fold or greater on sulcal and smooth surfaces. In in vitro experiments with samples of whole stimulated saliva, amylase expression did not affect S. mutans’ adherence to saliva-coated hydroxyapatite, and slightly increased S. mutans’ aggregation in solution (i.e., oral clearance). Conversely, S. mutans in biofilms formed in saliva with 1% glucose displayed no differences when cultured on polystyrene, but on hydroxyapatite was 40% less with amylase expression, suggesting S. mutans recognition of amylase bound to hydroxyapatite suppresses growth. However, this effect was overshadowed in vivo, as recoveries of S. mutans from dental plaque were similar between both groups of mice, suggesting amylase expression helps decrease plaque acids from S. mutans that dissolve dental enamel. With amylase deletion, commensal streptococcal species increased from approximately 75% to 90% of total oral microbiota, suggesting amylase may promote higher plaque pH by supporting colonization by base-producing oral commensals. Importantly, collective results indicate amylase may serve as a biomarker for caries risk.